Unveiling the social fabric through a temporal, nation-scale social network and its characteristics - Jolien Cremers; Benjamin Kohler; Benjamin Frank Maier; Stine Nymann Eriksen; Johanna Einsiedler; Frederik Kølby Christensen; Sune Lehmann; David Dreyer Lassen; Laust Hvas Mortensen; Andreas Bjerre-Nielsen (Scientific Reports)
Abstract Social networks shape individuals’ lives, influencing everything from career paths to health. This paper presents a registry-based, multi-layer and temporal network of the entire Danish population from 2008 to 2021. Our network maps the relationships formed through family, households, neighborhoods, colleagues and classmates for approximately 7.2 million individuals with more than 1.4 billion relations between them over the course of a decade. We outline key properties of this multiplex network, introducing both an individual-focused perspective as well as a bipartite representation. We show how to aggregate and combine the layers, and how to efficiently compute network measures such as shortest paths in large administrative networks. Our analysis reveals how past connections reappear later in other layers, that the number of relationships aggregated over time reflects the position in the income distribution, and that we can recover canonical shortest-path-length distributions when appropriately weighting connections. Along with the network data, we release a Python package that uses the bipartite network representation for efficient analysis.